Aneuploidy influences the gene expression profiles in Saccharomyces pastorianus group I and II strains during fermentation - Bond, Ursula; Hokamp, Karsten (My University, 2022)
The lager yeasts, Saccharomyces pastorianus, are hybrids of Saccharomyces cerevisiae and Saccharomyces eubayanus and are divided into two broad groups, Group I and II. The two groups evolved from at least one common hybridisation event but have subsequently diverged with Group I strains losing many S. cerevisiae chromosomes while the Group II strains retain both sub-genomes. The complex genomes, containing orthologous alleles from the parental chromosomes, pose interesting questions regarding gene regulation and its impact on the fermentation properties of the strains. Superimposed on the presence of orthologous alleles are complexities of gene dosage due to the aneuploid nature of the genomes. We examined the contribution of the S. cerevisiae and S. eubayanus alleles to the gene expression patterns of representative Group I and II strains during fermentation. We show that the relative expression of S. cerevisiae and S. eubayanus orthologues is positively correlated with gene copy number. Despite the reduced S. cerevisiae content in the Group I strain, S. cerevisiae orthologues contribute to biochemical pathways upregulated during fermentation which may explain the retention of specific chromosomes in the strain. Conversely, S. eubayanus genes are significantly overrepresented in the upregulated gene pool in the Group II strain. Comparison of the transcription profiles of the strains during fermentation identified both common and unique gene expression patterns, with gene copy number being a dominant contributory factor. Thus, the aneuploid genomes create complex patterns of gene expression during fermentation with gene dosage playing a crucial role both within and between strains.
PUBLISHED
cited By 0
Keywords: Saccharomyces pastorianus; Yeast; fermentation